(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
The articles and essays in this issue reflect a reckoning demanded by the disruption of the global pandemic. The contributing scholars have raised a number of local and global issues from within education, issues that have social ramifications beyond academe, from issues pertaining to what the world is going through such as trauma to resilience and need for adaptation, to wellbeing and success of both students and scholars guiding them, to ways to empower students and foster agency in the face of crisis, to structural racism and issues of justice and dignity for minoritized groups, to vocational learning for students and professional development for students to scholars, to issues in the discipline of music and engineering, to topics of technology and online education and topics about the post-covid world. The question that connects all of the contributions in this issue is: How can we overcome the crisis, as we also seek to address challenges and create opportunities that we see more clearly now? How do we seek new opportunities even as we counter problems that are exacerbated by this crisis? The authors collectively argue that this is a time for us to become more informed, aware, and sensitive to these challenges.